PENGEMBANGAN MATERI TENTANG KEMAMPUAN BERPIKIR POSITIF SISWA di SMP NEGERI 13 PEKANBARU - Fitri Yana; Raja Arlizon; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : In daily life, people always use their thinking power to solve the problems they face. The problem is solved with positive thinking. Therefore, the researcher feels the need to develop a material about Positive Thinking Ability of Student are expected to be used by guidance and counselling teachers to be taught to their students. This material is prepared using research and development (R & D) method. The purpose of this study is 1) The creation of material Positive Thinking Skills Stident viewed from clarity, systematics, images supported, upgrades, completeeness of material, and video/games. 2) To know the quality of material produced. This material is validated by leacturers 1 & 2, counselling teachers and 35 students of State Junior High School 13 Pekanbaru. This material is tested to students with allocation tie 3 hours lesson (4 x 40’). This material consists of understanding and Positive Thinking Theory, The Benefit of Positive Thinking, The Reality of Positive Thinking, How to Grow Positive Thoughts, How to Get Someone Applying the Concept of Positive Thinking in Life, and How to Grow positive Thinking Ability. The results of this material development show that the quality of the material produced is in the “Good” category, with a score of 4,08 for all aspects of the assessment.Keyword : Material Development, Ability, Positive Thinking